The financial structure of the fund - Kroc, Rudolf (Washington D.C. International Monetary Fund, 1967)
The first edition of this paper was based on two articles which appeared in the Fund and Bank Review, Finance and Development, Vol. II, No. 1 (March 1965) and Vol. II, No. 2 (June 1965). Changes in this present edition have been confined to bringing the paper up to date.
osc 29/01/2019
Loans
Keywords: International Monetary Fund; International Finance